Studi Literatur Tentang Integrasi Kearifan Lokal dalam Pembelajaran Bahasa Indonesia: Penelitian - Agung Nasrulloh Saputro (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to examine the integration of local wisdom in Indonesian language learning through a comprehensive literature review. The research background stems from the need to provide contextual, meaningful, and relevant learning to the socio-cultural environment of students. The research method uses a literature study approach by analyzing various scientific sources in the form of journals, books, and research reports published in the last ten years. The results of the study indicate that local wisdom has great potential in improving language skills, learning motivation, and understanding of students' cultural character. This integration has also proven effective in creating a more humanistic, interactive, and experience-based learning. Furthermore, this study identifies the need to strengthen the integration model that is more systematic and adaptive to curriculum development. These findings contribute by mapping strategies, challenges, and opportunities for developing Indonesian language learning based on local wisdom. Thus, this study is expected to serve as a reference for educators and researchers in designing learning that is responsive to the local cultural context.